Alternative treatment for open bite Class III malocclusion in a child with Williams-Beuren syndrome - Giovanni Modesto Vieira; Eduardo Jacomino Franco; Denise Falcão Pinheiro da Rocha; Laudimar Alves de Oliveira; Rivadávio Fernandes Batista Amorim (Dental Press Editora, 2015)
Williams-Beuren syndrome (WBS) is a rare genetic condition that affects approximately 1 in every 20,000 - 50,000 live births. WBS children have specific skeletal deformities, dental malformations and rare lingual muscle dysfunction. The need for orthodontic and orthognathic therapy has arisen and has been considered a real clinical challenge even for experienced professionals, once it requires a complex and individualized treatment plan. This study reports a case of orthopedic expansion of the maxilla, in which a modified facial mask was used for protraction of the maxillary complex associated with clockwise rotation of the maxilla. In addition, special considerations about treatment time and orthopedic outcomes are discussed.